Diagnostic potential of circulating miR-499-5p in elderly patients with acute non ST-elevation myocardial infarction - Olivieri, Fabiola; Antonicelli, Roberto; Lorenzi, Maria; D'Alessandra, Yuri; Lazzarini, Raffaella; Santini, Gabriele; Spazzafumo, Liana; Lisa, Rosamaria; La Sala, Lucia; Galeazzi, Roberta; Recchioni, Rina; Testa, Roberto; et al. (International journal of cardiology, 2013)
Geriatric patients with acute non-ST elevation myocardial infarction (NSTEMI) can frequently present atypical symptoms and non-diagnostic electrocardiogram. The detection of modest cardiac troponin T (cTnT) elevation is challenging for physicians needing to routinely triage these patients. Unfortunately, non-coronary diseases, such as acute heart failure (CHF), may cause cTnT elevation. Circulating microRNAs (miRs) have emerged as biomarkers of MI. However, their diagnostic potential needs to be determined in elderly NSTEMI patients. 92 NSTEMI patients (82.6±6.9years old; complicated by CHF in 74% of cases) and 81 patients with acute CHF without AMI (81.3±6.8years old) were enrolled at presentation. A third group comprised 99 age-matched healthy control subjects (CTR). Plasma levels of miR-1, -21, -133a, -208a, -423-5p and -499-5p were analyzed. MiR-1, -21 -133a and -423-5p showed a 3- to 10-fold increase and miR-499-5p exhibited >80-fold increase in acute NSTEMI patient vs. CTR. MiR-499-5p and -21 showed a significantly increased expression in NSTEMI vs. CHF. Interestingly, mir-499-5p was comparable to cTnT in discriminating NSTEMI vs. CTR and CHF patients. Its diagnostic accuracy was higher than conventional and hs-cTnT in differentiating NSTEMI (n=31) vs. acute CHF (n=32) patients with modest cTnT elevation at presentation (miR-499-5p AUC=0.86 vs. cTnT AUC=0.68 and vs. hs-cTnT AUC=0.70). Circulating miR-499-5p is a sensitive biomarker of acute NSTEMI in the elderly, exhibiting a diagnostic accuracy superior to that of cTnT in patients with modest elevation at presentation.